2019
DOI: 10.1016/j.apsb.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Hypericin enhances β-lactam antibiotics activity by inhibiting sarA expression in methicillin-resistant Staphylococcus aureus

Abstract: Bacteremia is a life-threating syndrome often caused by methicillin-resistant Staphylococcus aureus (MRSA). Thus, there is an urgent need to develop novel approaches to successfully treat this infection. Staphylococcal accessory regulator A (SarA), a global virulence regulator, plays a critical role in pathogenesis and β-lactam antibiotic resistance in Staphylococcus aureus. Hypericin is believed to act as an antibiotic, antidepressant, antiviral and non-specific kinase inhibitor. In the current study, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 55 publications
(84 reference statements)
2
28
0
Order By: Relevance
“…For each interaction, the fractional inhibitory concentration (FIC) was calculated for each agent: synergism, antagonism, and indifference correlated with FIC ≤ 0.5, FIC > 4, and 0.5 < FIC ≤ 4, respectively. 21 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each interaction, the fractional inhibitory concentration (FIC) was calculated for each agent: synergism, antagonism, and indifference correlated with FIC ≤ 0.5, FIC > 4, and 0.5 < FIC ≤ 4, respectively. 21 …”
Section: Methodsmentioning
confidence: 99%
“… 23 Delivering approximately 5×10 5 CFU*mL −1 of MRSA cells to 96-well plates containing diluted BER and antibiotics in brain heart infusion broth (BHI, OXIOD) supplemented with 0.5% glucose. 21 Wells containing only the BHI were used as the negative control, whereas wells containing bacteria grown in BHI were used as the positive control. The suspension was transferred to 96-well plates with individual compounds and combinations (4 × MIC, 2 × MIC, 1 × MIC, 1/2 × MIC, 1/4 × MIC of BER, 1/16 × MIC, 1/32 × MIC of RIF, or 1/4 × MIC of CLI) treated and incubated for 18 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…These combinations completely inhibited the growth of bacteria after 24 h (Joung et al, 2015). Studies have found that hypericin and β-lactam antibiotics such as oxacillin have anti-MRSA ability (Wang et al, 2019). Cha et al (2014) demonstrated that cryptotanshinone combined with ampicillin, oxacillin, or vancomycin had synergistic effects on methicillin-resistant and vancomycinresistant S. aureus and greatly inhibited the growth of bacteria.…”
Section: Quinones Combined With Antibiotics For Antibacterial Effectsmentioning
confidence: 99%
“…Staphylococcal accessory regulator A (SarA), a global virulence regulator, plays a critical role in pathogenesis and β-lactam antibiotic resistance in S. aureus 122 - 124 . Interestingly, antidepressant and antiviral hypericin was found to significantly reduce sarA , mecA and virulence-related regulator expression, thereby enhancing the activity of β-lactam antibiotics against MRSA 125 .…”
Section: Recent Successes In the Fight Against Superbugsmentioning
confidence: 99%